Rational points on a certain genus 2 curve - Nguyen, Xuan Tho (Comptes Rendus. Mathématique, 2023)
We give a correct proof to the fact that all rational points on the curve \[ y^2=(x^2+1)(x^2+3)(x^2+7) \] are $\pm \infty $ and $(\pm 1,\,\pm 8)$. This corrects previous works of Cohen [3] and Duquesne [4, 5].